(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s economy has been mostly dependent on agriculture from the ancient era. India experienced a catastrophic food crisis in the 1950s known as the "Bengal Famine." Relatively speaking, agricultural planning has increased crop yields throughout time. The term "The Green Revolution" refers to the phase of agricultural development in which fertilizers, chemicals, pesticides, are used to increase the foodgrain production through the High Yield Varieties (HYV) seeds. The production of rice and wheat has gone up during the green revolution period in India and India becomes self reliance in terms of foodgrains. The term "green revolution" describes the rise in agricultural output brought about by the development of highyielding seed varieties (HYVS), better water management techniques, the application of chemical herbicides and fertilizers, and extensive technology support. India’s agriculture sector has benefited greatly from the Green Revolution. For example the production of foodgrain not only increased but India becomes one of the exporters of food grain. Due to green revolution, production, productivity and farmers income has changed positively. Nonetheless, the majority of people in the country have health issues raised due to excessive use of pesticides and chemicals in agriculture sector. Likewise malnourishment is increasing because poor nutrition value of food grains and excessive fertilizer consumption. The green revolution has also adversely affected on the soil fertility and environmental resources like water and air. Under this backdrop, present study attempted to examine both positive as well as negative influence of green revolution in India.